Translation and Validation Study of the First Modified Pakistani Version of the Neck Disability Index and its Revalidation (Medical Forum Monthly, 2024)
Objective: The purpose of our study was the translation and validation of the Neck Disability Index in our specific cultural background. The Pakistani Urdu version of Neck Disability Index (NDI) was tested for validity and reliability. The Neck Disability Index (NDI) is a valid and reliable tool, designed to measure disability in routine life activities due to neck pain. International standards were followed for the translation strategy comprising forward translations, reconciliation, backward translation and pre-testing steps. The translation of the original questionnaires was performed in accordance with published guidelines and this was adapted to cultural differences in the patient population. These procedures resulted in the Pakistani modified version of the NDI.Study Design: comparative study.Place and Duration of Study: This study was carried out at the Department of Neurosurgery Outdoor Clinics at Benazir Bhutto Shaheed Teaching Hospital Abbottabad from April 2007-March 2009.Materials and Methods: In the first stage, Fifty five patients (32 men, 23 women) were included over two years period at the Department of Neurosurgery Outdoor Clinics at Benazir Bhutto Shaheed Teaching Hospital Abbottabad attached with Women Medical College Abbottabad. Seventeen patients were suffering from acute phase after a neck sprain, 20 had chronic neck pain and 18 had no neck pain but had other musculoskeletal symptoms. On 3 occasions, the patients completed the Neck Disability Index and other surveys. Levels of sensitivity, test-retest reliability and validity were acceptable. In the next stage, Thirty-eight patients (16 men, 22 women) were included in a study of the modified version, twenty patients with acute neck sprain and 18 with other musculoskeletal symptoms filled out to test the modified version of the Neck Disability Index, which provided a more specific measure of disability due to neck pain.Results: We have accumulated enough evidence to show that the Urdu version of the Neck Disability Index measures disability in activities of daily living in patients with neck pain in a reliable, valid and responsive manner. The questionnaire is considered a useful tool for research and clinical settings in local or international studies since its psychometric properties are comparable with other versions validated in different countries.Conclusion: The Pakistani version of NDI is a reliable and valid instrument to measure psychometric properties and functional status in Pakistani patients suffering from neck disability. Being a simple and fast scale, its use can be recommended in a clinical setting and future outcome studies in Pakistan